Civil society and informal mechanisms of transitional justice : filling the gap of accountability and acknowledgement for the 2008 electoral violence in Zimbabwe - Nathan, Laurie (University of Pretoria, 2016)
Dissertation (MA)--University of Pretoria, 2015.